GEOLOGI DAN STUDI ALTERASI HIDROTERMAL DAERAH NGADIROJO DAN SEKITARNYA, KABUPATEN PACITAN, PROVINSI JAWA TIMUR - Qosim Ghozali, Nur
The research area is located in Ngadirojo, Kluwih, and Tulakan Sub-District, Pacitan Regency, East Java. The geographic coordinate are located at 532692–540972 mE and 9091566–9099043 mN, within an area around 56.66 km2. The research area is part of a Southern Mountain Zone that is composed by Tertiary rock. The objectives of this research are gained by doing geological mapping, petrographic and mineragraphic analysis observation, and secondary data analysis using Analytical Spectral Device (ASD). The research area generally had geomorphological expression of volcanic environment, that is divided into five units, including Lava Flow Hills of Nogosari Unit, Lava Flow Ridge of Bodag Unit, Plateau of Sudimoro Unit, Alluvial Plain of Ngadirojo Unit, and Lava Flow Dome of Pagerejo Unit. Stratigraphy’s research area consists of eight rock units, from the oldest to the youngest including, Andesite Lava Unit 1, Pyroxene Andesite Lava Unit, Polymic Breccia Unit, Andesite Lava Unit 2, and Dacite Lava Dome Unit, wich has a conformity stratigraphic relations and deposited at Late Oligosen–Early Miosen in marine environment. Sandstone Unit desposited in transition environment and interfingering with Limestone Unit wich deposited in inner neritic–middle neritic. Those units had disconfomity relatioship with all previous units and deposited at Middle Miosen. Alluvium Deposit unit had disconformity relationship with all previous units and deposited at Resen. The strike of the rock layer in this research area are generally northwest–southeast with a dip to the southwest. The main structures trend northeast–southwest as thrust left slip formed at Early Miosen and Middle Miosen. Hydrothermal alteration zones that developed from Chlorite-Epidote-Calcite±Quartz zone that overprinted by Quartz-Illite±Paragonite±Muscovite Zone and deposited Quartz- Dickite-Pyrophyllite±Illite Zone, Quartz-Illite±Dickite±Kaolinite Zone, and Ilite-Kaolinite- Quartz±Montmorilonite Zone in accordance with the hydrothermal fluid. The formation temperaturs of forming alteration minerals range from 140–320°C, which is within epithermal system temperature. Pyrite occure in all in alteration zone ande enargitecovellite- chalcopyrit-tetrahedrite-magnetite-chalcocite-chalcopyrite-malachite-azurite occure in Quartz-Dickite-Pyrophyllite±Illite Zone and Quartz-Illite±Paragonite±Muscovite Zone. Minerlization the research area are hypogene and supergene. Alteration mineral and mineralization found in the research area interpretted as high sulphidation epithermal deposit system within deep level caused by erotion.